A case report: combined posterior subthalamic area and globus pallidus internus deep brain stimulation in Parkinson’s disease - Deng, Qi; Zou, Yanghong; Yuan, Yingwang; Geng, Xin (Frontiers in Human Neuroscience, 2025)
BackgroundDeep brain stimulation is a primary surgical treatment for advanced Parkinson’s disease (PD). The globus pallidus interna (GPi) is a key target for this procedure. The posterior subthalamic area (PSA) serves as an effective target for tremor-dominant Parkinson’s disease. However, it is less commonly utilized in conventional DBS surgery compared to the subthalamic nucleus (STN) or the ventral intermediate nucleus (VIM). There is currently no clinical research on the combined DBS surgery targeting both the PSA and the GPi, which is why we have conducted this study.Case reportWe introduced a case of a patient with advanced PD. Due to the patient’s primary manifestations of right-sided tremor and left-sided rigidity, along with significant dyskinesia on the left side, DBS implantation was performed in the left hemisphere targeting the PSA and in the right hemisphere targeting the GPi. The patient’s UPDRS-III score decreased from 73 to 46 postoperatively, showing an improvement of approximately 36.99%, while the H-Y stage improved from stage 4 to 2.5, representing a 37.5% improvement. During the 6-months postoperative follow-up, the patient’s PD symptoms were effectively controlled, with no significant adverse effects.DiscussionWhen advanced PD patients present with asymmetric and variable motor symptoms, combined DBS stimulation targeting both the GPi and the PSA is a viable treatment option.